2019
DOI: 10.1039/c9ra03582f
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-based separation mechanism for waste crystalline silicon photovoltaic modules by a two-stage heating treatment

Abstract: A two-stage heating treatment was conducted to separate the waste crystalline silicon solar panels. The TPT backing materials were recovered integrally by heating at 150 °C, and the EVA binder was removed at the temperature of 500 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The outcome of the respective processes shows a great variety including a simple procedure of crushing the panels 3–6 and reusing the impure remnants as a material feedstock for the industry. More advanced procedures utilize more careful techniques for the separation of the individual layers with organic solvents 7–9 or thermal methods 10–12. Moreover, copper and silver can be recovered by hydrometallurgic processes, mainly with nitric acid 10, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of the respective processes shows a great variety including a simple procedure of crushing the panels 3–6 and reusing the impure remnants as a material feedstock for the industry. More advanced procedures utilize more careful techniques for the separation of the individual layers with organic solvents 7–9 or thermal methods 10–12. Moreover, copper and silver can be recovered by hydrometallurgic processes, mainly with nitric acid 10, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a pyrolysis process for delamination (e.g. Dias et al, 2016;Wang et al, 2019) has been investigated as well. Finally, thermal processes have also been explored as an integrated step in PV recycling processes, not as a delamination step but rather after mechanical crushing (Ardente et al, 2019;Pagnanelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic triplet can benefit reactor design, process modeling of the pyrolysis delamination of PV modules, and aid in the scaling up of the effective recycling processes. To the best of the authors’ knowledge, two existing kinetic studies on the EVA encapsulant were found in c-Si PV modules from De-wen et al and Wang et at. , These studies reported activation energies 15 years apart, but differ considerably from one another in terms of results, kinetic modeling methods used, and did not evaluate the kinetic triplet. This could be due to experimental error, a difference in the grade of EVA used in the study, or the kinetic modeling method employed in their study.…”
Section: Introductionmentioning
confidence: 99%